TMPRSS2 as a Key Player in Viral Pathogenesis: Influenza and Coronaviruses - Gilmara Barros de Lima; Everton Nencioni; Fábio Thimoteo; Camila Perea; Rafaela Fuzaro Alves Pinto; Sergio Daishi Sasaki (Biomolecules)
TMPRSS2, a human transmembrane protease enzyme, plays a crucial role in the spread of certain viruses, including influenza and coronaviruses. This enzyme promotes viral infection by cleaving viral glycoproteins, which helps viruses like SARS-CoV-2 and influenza A enter cells more effectively. Genetic differences in TMPRSS2 may affect people’s susceptibility to COVID-19, underscoring the need for studies that consider diverse populations. Beyond infectious diseases, TMPRSS2 has also been linked to some cancers, suggesting it could be a valuable target for drug development. This review provides a summary of TMPRSS2 inhibitors currently under study, with some already in clinical trials to test their effectiveness against viral infections. As we uncover more about TMPRSS2’s role in pathogenesis, it could open new doors for therapies to combat future outbreaks.